A Review on Data Center Networking and Security Aspects in Cloud: Examining the challenges and solutions in data center networking for cloud computing (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cloud computing is an evolving paradigm of technology that translates existing technical and computing ideas into utilities comparable to water and electricity systems. Data Center Networks (DCN) is the most important infrastructure for cloud computing's success. In the creation and management of a reliable cloud service, a scalable efficient data center (DC) is essential. During the last several years, the increasing significance of networking data centers has highlighted associated problems such as conjunctive simplicity and service reliability. The agility needed for multi-tenant cloud requirements is lacking in existing DCNs, leading to poor responsively and reduced scalability. Several security privacy issues need to be addressed in the cloud computing environment. In this work, we provide an overview of Cloud Computing (CC) also its classification. DCN for CC evaluate construction prototypes depends upon these issues. This paper summarizes an outline of the data center network for CC, DCN for service models, and deployment models for cloud data centers (DCs) to decrease server power consumption. This comprehensive study also develops and analyses the many unsolved problems impeding the adoption and spread of cloud computing by the different stakeholders involved.